A CoII-Hydroxide Complex That Converts Directly to a CoII-Acetamide during Catalytic Nitrile Hydration - Mc Donald, Aidan (My University, 2024)
In exploring structural and functional mimics ofnitrile hydratases, we report the synthesis of the pseudo-trigonalbipyramidal CoII complexes (K)[CoII(DMF)(LPh)] (1(DMF)),(NMe4)2[CoII(OAc)(LPh)] (1(OAc)), and (NMe4)2[CoII(OH)-(LPh)] (1(OH)) (LPh = 2,2′,2’’-nitrilo-tris-(N-phenylacetamide;DMF = N,N-dimethylformamide; −OAc = acetate)). Thecomplexes were characterized using NMR, FT-IR, ESI-MS,electronic absorption spectroscopy, and X-ray crystallography,showing the LPh ligand to bind in a tetradentate tripodal fashionalongside the respective ancillary donor. One of the complexes,1(OH), is an unusual structural and functional mimic of the Coactive site in Co nitrile hydratases. 1(OH) reacted with acetonitrile to yield the CoII-acetamide complex (NMe4)2[CoII(NHC-(O)CH3)(LPh)], 2, which was also thoroughly characterized. In the presence of excess hydroxide, 1(OH) was found to catalyzequantitative conversion of the added hydroxide into acetamide. Despite the differences in Co oxidation state in nitrile hydratases and1(OH) (CoIII versus CoII, respectively), 1(OH) was nonetheless an effective nitrile hydration catalyst, selectively producingacetamide over multiple turnovers
PUBLISHED
Keywords: nitrile hydratases; pseudo-trigonalbipyramidal CoII complexes; electronic absorption spectroscop